The Influence of Knowledge Management, Work Discipline, and Organizational Culture on Occupational Health and Safety (OHS) Implementation at PT Nihon Chemical Indonesia - Ova Perdanawati; Soehatman Ramli; Adenan Adenan; Edison Sembiring (Rifa'Institute, 2026)
Introduction: Occupational Health and Safety (OHS) implementation remains a critical issue in industrial sectors, particularly in developing countries where workplace accidents continue to increase despite regulatory frameworks. Objective: This study aims to examine the influence of knowledge management, work discipline, and organizational culture on OHS implementation at PT Nihon Chemical Indonesia. Method: A quantitative approach with an explanatory research design was employed, using primary data collected through questionnaires distributed to employees and analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. Result: The findings indicate that knowledge management, work discipline, and organizational culture have positive and significant effects on OHS implementation, both partially and simultaneously, with organizational culture identified as the most dominant factor. Conclusion: The integration of these three factors plays a crucial role in improving OHS implementation, emphasizing that workplace safety is influenced not only by formal regulations but also by behavioral and organizational dimensions, while also providing empirical contributions and practical insights for strengthening safety performance in the Indonesian chemical industry